Hubungan Pengetahuan, Sikap dan Karakteristik Tempat Perindukkan Nyamuk dengan Keberadaan Jentik Aedes Aegypti di Kota Depok: The Relationship Between Knowledge, Attitude, and Breeding Site Characteristics with the Presence of Aedes aegypti Larvae in Depok City - Herawati, Asri; Sari, Agustina; Sulistyorini, Desy (MPI Press, 2024)
Introduction: Dengue Hemorrhagic Fever is caused by the Aedes aegypti mosquito. The presence of Aedes aegypti larvae is an indicator of the presence of Aedes aegypti mosquitoes in the area Objectives: The purpose of this study was to determine the relationship between Knowledge, Attitudes and Characteristics of Mosquito Breeding Sites and the Presence of Aedes Aegypti Larvae in Depok City in 2023 Method: This study used a quantitative research type with a cross-sectional design totaling 100 respondents in people living in Depok city. Accidental sampling technique. The data used are primary data through questionnaires and observations and secondary data derived from books and literature. Data analysis was performed univariately and bivariately with the Chi-Square Test Result: The results showed that there was a relationship between knowledge (p-value = 0.044), attitude (p-value = 0.000), location (p-value = 0.000), color (p-value = 0.000) and the availability of container lid (p-value = 0.000) in the presence of Aedes aegypti larvae. However, there is no relationship between the container material and the presence of Aedes aegypti larvae with a p-value of 0.225 Conclusion: there is a relationship between knowledge (p-value = 0.044), attitude (p-value = 0.000), location (p-value = 0.000), color (p-value = 0.000) and the availability of container lid (p-value = 0.000) in the presence of Aedes aegypti larvae. However, there is no relationship between the container material and the presence of Aedes aegypti larvae with a p-value of 0.225